DESIGNING NEWS ONLINE WITH DYNAMIC WEB TELEVISION FOR USING IN PHP AND MYSQL LINUX OS FEDORA CORE 6 - Endro Purwanto (Jurnal Sistem Informasi, 2008)
The development of television is so fast and was accompanied by  reporters appearance of a reliable news seekers, is one  very good composition. With this scientific writing hopefully be an inspiration for the television world of Indonesia to deliver not only television news only. The Internet is a medium which can also be used for the delivery of news using a website. According to observations by the author today, making this website only uses the php programming language and MySQL database. Many people who do not have time to watch television news because  intensive activities. Old news that even need a filing, it aims to facilitate the search for news returned if needed. In scientific writing, the writer has managed to create a database design that can be connected to the php programming language. The authors give the name of the database dbkkp and had eleven tables. But not all the tables are the authors discussed here. The design has become a ready-made applications after repeatedly testing the program authors. Television world and the news will not be separated, to deliver information quickly and clearly was through this medium. But if there are still people who can not watch the news on television it would be nice to help them communicate using other media.